Intervertebral kinematics during neck motion 6.5 years after fusion and artificial disc replacement. (October 2022) - Yeni, Yener N.; Azad, Sherwin; Oravec, Daniel; Schildcrout, Andrew; Basheer, Azam; Bey, Michael J.; Bartol, Stephen W.; Chang, Victor
Abstract: Background: Arthroplasty with artificial disc replacement for surgical treatment of cervical spine degeneration was introduced with the notion that motion-preserving approaches would prevent development of adjacent segment disease. Though clinical outcomes favor arthroplasty over the commonly used anterior cervical discectomy with fusion approach, clinical studies confirming the biomechanical basis of these results are lacking. The aim of this study was to compare intervertebral kinematics between arthroplasty and fusion patients 6.5 years post-surgery during physiological motion of the neck. Methods: Using a biplane dynamic X-ray system, computed tomography imaging and model based tracking algorithms, three dimensional intervertebral kinematics were measured during neck axial rotation and extension in 14 patients treated for cervical radiculopathy with fusion ( n  = 8) or arthroplasty ( n  = 6). The measurements were performed at 2-year (baseline) and 6.5 year post-surgical time points, with the main interest being in the interaction between surgery types and time points. 3 translations and 3 rotations were investigated for the index (C5C6), and upper- (C4C5) and lower adjacent levels (C6C7). Findings: Surgery-time interaction was significant for axial rotation ( P  < 0.04) and flexion-extension rotation ( P  < 0.005) in C4C5 during neck axial rotation, left-right translation ( P  < 0.04) in C5C6 and anterior-posterior translation in C6C7 ( P  < 0.04) during neck extension. In contrast with the expectations, axial rotation and flexion-extension decreased in C4C5 during neck rotation and anterior-posterior translation decreased in C6C7 during neck extension for fusion. Interpretation: The findings do not support the notion that adjacent segment motion increases after fusion. Highlights: Adjacent segment disease is believed to occur when motion is limited at index level. We measured how kinematics change over time after fusion or arthroplasty at C5C6. Axial rotation at C4C5 superior to fusion decreased over time in neck axial rotation. Anteroposterior translation at C6C7 decreased over time in neck extension for fusion. Increased adjacent segment motion in fusion causing further disease is not supported.